The Effect of Interest, Digital Skills, and Campus Teaching Programs on Prospective Teachers’ Professional Competence - Vebriyanti, Lioni; Prasetiyo, Wibowo Heru (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to demonstrate that interest, digital skills, and the Campus Teaching Program can enhance the professional competence of prospective teachers, equipping them with essential skills for their future teaching careers. Methodology: This study employed a quantitative method with a correlational design. The sample consisted of 77 students who participated in the Campus Teaching Program, batches 6 and 7. Results: The results of the analysis show that interest, digital skills, and the Campus Teaching Program have a positive and significant correlation to the professional competence of prospective teachers. A strong interest in becoming a teacher leads to greater enthusiasm for deepening knowledge. Moreover, the Campus Teaching Program offers direct field experience, where prospective teachers are trained to thoroughly understand lesson content, engage positively with students, and apply innovative, technology-integrated teaching methods. Applications/Originality/Value: This study contributes to the literature on education, particularly in preparing prospective teachers to enhance their professional competence. Furthermore, future research can utilize this data to develop theories, findings, and hypotheses for subsequent investigations.